Students’ Perception of Infographics: A Visualization Tool on Strengthening Critical Thinking Skills - Dewi, I Gusti Ayu Triska Sri Urmila; Padmadewi, Ni Nyoman; Marsakawati, Ni Putu Era; Artini, Luh Putu; Ratminingsih, Ni Made; Utami, IGA Lokita Purnamika (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
As previous studies showed the effectiveness of infographic, it is important to find out students’ perception the use of infographic especially on its relation to critical thinking as on of the 21st century skills students require. Therefore, this study purposed to analyze students’ perception towards the use of infographics as a visualization tool to strengthen critical thinking. The study employed a descriptive quantitative research method by using questionnaire and semi-structured interview to collect the data, which included ten statements for the questionnaire and five questions for the interview. The participants in this study were 34 students of elevent grade students. The findings showed that the majority of students had a favorable opinion of using Infographics as a visualization tool in the learning process. Most students said learning with infographics provided them with a new learning environment. Moreover, they felt interested when they studied with infographics as it gave clear information they needed. Futhermore, the students stated that by using infographics, they can enhance their critical thinking skills compared to when they were not using infographics as a visualization tool during the learning process.